Pelaksanaan SL-PTT Dan Peran Penyuluh Terhadap Petani Kakao Di Kecamatan Bandar Baru Kabupaten Pidie Jaya - Wardah, Eva; Budi, Setia (LPPM Universitas Malikussaleh - Indonesia, 2018)
This study aims to determine the application of SL-PTT to smallholder cocoa farmers and the role of agricultural extension agents in cocoa cultivation activities in Banda Baru Sub District, Pidie Jaya District. This research uses survey method. Primary data was obtained from structured interviews (quisioner) while secondary data were obtained from various agencies that were related to this research. Data were analyzed quantitatively and qualitatively and described in the results of the study. The results showed that the majority of members of the Cocoa farmer group were productive working age for farming, the majority only had formal junior high school education level (SLTP). More than half of Cocoa farmers have a family burden of 3-5 people. The land area of kakao farmers is in the medium category (1-3 Ha). The application of SL-PTT in the People's Cocoa Farming is in the role category. Furthermore, the role of instructors as initiators, mediators, facilitators is in the very instrumental category, while the role of instructors as dynamicators and organizers is in the role category. Strengthening is needed for extension agents, especially in terms of strengthening farmer group institutions and the ability and skills to motivate farmer group members to implement innovations offered by extension workers in cocoa farming activities